A New Micro-composite Material of Micro-particle Amalgam/Polyvinyl Alcohol for Teething Structures - Abas, Falak O.; Abass, Raghad U. (Iraqi Journal of Science, 2019)
Dental amalgam is a mixture of approximately 50% mercury and varying ratios of silver, tin, zinc, and copper. Dental amalgam is a major source of mercury pollution because it is readily absorbed through 90-100% vapour and the oral mucosa. In addition, in certain situations with the oral environment, various types of metallic orthodontic brackets are highly aggressive and can lead to corrosion. However, polyvinyl alcohol (PVA) material has no cytogenetic effects on human health or the environment and is therefore applied in the manufacturing of the new composite material. Different additives from the bonding agent (PVA; 2.4, 4.8, and 7.2 g) dissolved in about 10 ml of water, heated on a hot plate under a high-temperature heat treatment (150-200 á´¼C), and continuously stirred for about 20 minutes, until all the PVA dissolved or the solution became colorless. Subsequently, a fixed amount of powdered amalgam (2.4g) added after the mercury content was separated. It was continuously mixed until it reached a homogenous solution, then molded and cured to give the final product. New samples were used for the following purposes: (1) to investigate their effects on the chemical, thermal and mechanical properties of the composite samples, (2) composite scanning and images from the EDS diffraction. Scanning lectron microscopy (SEM) indicated that the presence of the methyl group (CHI) that lowers the crystallinity of PVA, also forms bridges between the different chains obtained to indicate the suitable materials for guided dental applications.